2014
DOI: 10.1007/s12035-014-8818-2
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Misfolding Versus Aggregation Relevance to Parkinson’s Disease: Critical Assessment and Modeling

Abstract: α-Synuclein, an abundant and conserved presynaptic brain protein, is implicated as a critical factor in Parkinson's disease (PD). The aggregation of α-synuclein is believed to be a critical event in the disease process. α-Synuclein is characterized by a remarkable conformational plasticity, adopting different conformations depending on the environment. Therefore, it is classified as an "intrinsically disordered protein." Recently, a debate has challenged the view on the intrinsically disordered behavior of α-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…The aggregation of αS is closely related to several neurodegenerative diseases including Parkinson’s disease (PD) [1, 3]. Recently it was found that αS was present in aggregates of the Krabbe disease and apparently prone to fibrillization in the presence of psychosine [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aggregation of αS is closely related to several neurodegenerative diseases including Parkinson’s disease (PD) [1, 3]. Recently it was found that αS was present in aggregates of the Krabbe disease and apparently prone to fibrillization in the presence of psychosine [4].…”
Section: Introductionmentioning
confidence: 99%
“…αS adopts different conformations under various environments. Under physiological conditions, αS is characterized as an intrinsically disordered protein, exhibiting a random coil conformation in aqueous solution [3]. In the presence of the membrane, αS displays an α-helical secondary structure as observed from solution NMR structure of micelle-bound αS [5, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that this protein is involved in normal synaptic transmission, successfully modulating α‐Syn synthesis in sporadic cases can be challenging. High intracellular levels of α‐Syn may increase its tendency to aggregate, together with other factors such as protein misfolding, limited proteolysis, mutations, and post‐transcriptional modifications such as phosphorylation and truncation . The processes of α‐Syn aggregation and fibrillation can be used as therapeutic targets for the development of drugs that act as conformational stabilizers and anti‐aggregation agents (e.g., small molecules, rifampicin).…”
Section: Therapeutic Alternatives For Synucleinopathiesmentioning
confidence: 99%
“…The accumulation and aggregation of α-syn is likely contributing to PD progression. The α-syn variant A53T (53 A→T) found in human patients has no effect on osmotic stress-induced phosphorylation, but increases oligomerization and exacerbates disease progression; suggesting a causal relationship between α-syn oligomerization and PD (Berrocal, Vasquez et al, 2014 ). Consistently, recent work suggested that monomeric α-syn level is likely reduced in cerebrospinal fluid (CSF) of the PD patients, while the oligomeric α-syn may increase (Aasly, Johansen et al, 2014 ).…”
mentioning
confidence: 99%